Development of a Training Program for Pre-Service English Teachers on English Camp Innovation to Enhance Secondary School Students’ Communicative Skills - โมรา จตุพงค์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to 1) develop a training program for pre-service English teachers focusing on English Camp Innovation, 2) enhance their ability to design activities based on the concept of English Camp Innovation, 3) examine the effects of English camps based on English Camp Innovation on secondary school students’ communicative skills, and 4) evaluate the satisfaction and usefulness of the training program on English Camp Innovation. This study employed a research and development (R&D) approach. The population consisted of 54 fourth-year pre-service English teachers from Faculty of Education and 76 lower secondary school students. The research instruments included a training program, an English camp activity design ability assessment form, a communicative skills assessment form, and a program effectiveness evaluation form. Data were analyzed using mean, standard deviation, and t-test. The findings revealed that 1) the training program was rated at the highest level of suitability, 2) the pre-service teachers’ ability to design English camp activities after the training was significantly higher than before the training at the .05 level, 3) the students’ communicative skills after participating in the English camp were significantly higher than before participation at the .05 level, and 4) the training program demonstrated a high level of satisfaction and usefulness in enhancing the pre-service teachers’ confidence, teaching competence, and innovative skills. The results suggest that a training program emphasizing English camp innovation can effectively enhance pre-service teachers’ competencies and improve students’ communicative skills.